Comparative Transcriptome Assembly and Genome-Guided Profiling for Brettanomyces Bruxellensis lamap2480 During P-Coumaric Acid Stress - Martinez-Fernandez, C; Ganga-Munoz, M; Godoy-Olivares, L (Nature Publishing Group, 2016)
Brettanomyces bruxellensis has been described as the main contaminant yeast in wine production, due to its ability to convert the hydroxycinnamic acids naturally present in the grape phenolic derivatives, into volatile phenols. Currently, there are no studies in B. bruxellensis which explains the resistance mechanisms to hydroxycinnamic acids, and in particular to p-coumaric acid which is directly involved in alterations to wine. In this work, we performed a transcriptome analysis of B. bruxellensis LAMAP248rown in the presence and absence of p-coumaric acid during lag phase. Because of reported genetic variability among B. bruxellensis strains, to complement de novo assembly of the transcripts, we used the high-quality genome of B. bruxellensis AWRI1499, as well as the draft genomes of strains CBS2499 and0 g LAMAP2480. The results from the transcriptome analysis allowed us to propose a model in which the entrance of p-coumaric acid to the cell generates a generalized stress condition, in which the expression of proton pump and efflux of toxic compounds are induced. In addition, these mechanisms could be involved in the outflux of nitrogen compounds, such as amino acids, decreasing the overall concentration and triggering the expression of nitrogen metabolism genes. © 2016 The Author(s).